PENGARUH MANAJEMEN STRATEGIK TERHADAP PENINGKATAN KINERJA GURU DAN SISWA DI SMAN 1 KARAU KUALA - Simanjuntak, Robet Januar; Suriansyah, Ahmad; Purwanti, Ratna (STKIP Pesisir Selatan, 2025)
Strategic management is a systematic approach that is very important in improving the quality of education, especially in the context of curriculum changes and the demands of 21st century competencies. Teachers are required to have high professional and pedagogical competencies and be able to apply innovative learning methods. This study aims to examine the implementation of strategic management at SMAN 1 Karau Kuala and analyze its influence on teacher and student performance. Using qualitative descriptive methods, this study describes the basic concepts of strategic management, its implementation at the school level, and its impact on teacher professionalism and student achievement. The results of the study indicate that consistent implementation of strategic management can improve the quality of planning and implementation of learning by teachers, as well as create a conducive and adaptive learning environment for students. Strategic management has also been shown to strengthen internal collaboration, increase resource efficiency, and foster an innovative and quality-oriented work culture. Therefore, strategic management can be used as the main foundation in creating superior and highly competitive schools in the modern era.